THE Representasi Rasisme pada Manga Shingeki No Kyojin Karya Isayama Hajime - Manurung, Leonita Rafeline; Ari Sulatri, Ari Sulatri; Oeinada, I Gede (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2024)
This study aims to determine the types of racism and the impact of racism depicted in Isayama Hajime's Shingeki no Kyojin manga. The data collection method was carried out using the documentation method and supported by the Listen and Note technique, as well as data analysis using a qualitative descriptive method, and presenting data analysis using an informal method. This study uses sociological theory according to Alan Swingewood and the theory of racism according to Beverly Daniel Tatum. Based on the research results, it is known that there are representations in the form of types of racism in the Shingeki no Kyojin manga. This can be seen in the Eldian race which was oppressed by the ruling party, namely the Marleyan race and it can be understood that the types of racism are categorized by (1) individual racism, (2) cultural racism, and (3) institutional racism. Furthermore, the results of the analysis regarding the impact of racism depicted in the Shingeki no Kyojin manga found the emergence of resistance movements, inner conflicts in the Eldian race, and differences of opinion between individuals.